(untitled) (Faculty of Education Scientific Journal, 2024)
The focus lies on ensuring the security and confidentiality of information, particularly in light of the threat posed by hackers who can gain unauthorized access to private data belonging to individuals and institutions. Therefore, it is imperative that information be encoded in a manner that conceals it effectively. To address this issue, encryption emerges as a viable solution for safeguarding messages and shared online information. This research proposes the utilization of encryption and decryption techniques based on a mathematical model. Specifically, the unary Kushare integral transform and the binary Laplace-Kushare transform are employed for encrypting plaintext, along with their corresponding inverse transforms for decryption. This approach serves as a means of fortifying information against intrusion, with practical applications in utilizing the aforementioned mathematical models for encryption and decryption processes.